PL3.6 Targeting GSK-3 activity promotes mitotic catastrophe via centrosome destabilisation and enhances the effect of radiotherapy in glioma models. (6th September 2019) - Bruning-Richardson, A; Sanganee, H; Barry, S; Tams, D; Brend, T; King, H; Morton, R; Ward, T; Steele, L; Shaw, G; Esteves, F; Droop, A; et al.
Abstract: BACKGROUND: Targeting kinases as regulators of cellular processes that drive cancer progression is a promising approach to improve patient outcome in GBM management. The glycogen synthase kinase 3 (GSK-3) plays a role in cancer progression and is known for its pro-proliferative activity in gliomas. The anti-proliferative and cytotoxic effects of the GSK-3 inhibitor AZD2858 were assessed in relevant in vitro and in vivo glioma models to confirm GSK-3 as a suitable target for improved single agent or combination treatments. MATERIAL AND METHODS: The immortalised cell line U251 and the patient derived cell lines GBM1 and GBM4 were used in in vitro studies including MTT, clonogenic survival, live cell imaging, immunofluorescence microscopy and flow cytometry to assess the cytotoxic and anti-proliferative effects of AZD2858. Observed anti-proliferative effects were investigated by microarray technology for the identification of target genes with known roles in cell proliferation. Clinical relevance of targeting GSK-3 with the inhibitor either for single agent or combination treatment strategies was determined by subcutaneous and orthotopic in vivo modelling. Whole mount mass spectroscopy was used to confirm drug penetration in orthotopic tumour models. RESULTS: AZD2858 was cytotoxic at low micromolar concentrations and at sub-micromolar concentrations (0.01 - 1.0 μM) induced mitotic defects in all cell lines examined. Prolonged mitosis, centrosome disruption/duplication and cytokinetic failure leading to cell death featured prominently among the cell lines concomitant with an observed S-phase arrest. No cytotoxic or anti-proliferative effect was observed in normal human astrocytes. Analysis of the RNA microarray screen of AZD2858 treated glioma cells revealed the dysregulation of mitosis-associated genes including ASPM and PRC1, encoding proteins with known roles in cytokinesis. The anti-proliferative and cytotoxic effect of AZD2858 was also confirmed in both subcutaneous and orthotopic in vivo models. In addition, combination treatment with AZD2858 enhanced clinically relevant radiation doses leading to reduced tumour volume and improved survival in orthotopic in vivo models. CONCLUSION: GSK-3 inhibition with the small molecule inhibitor AZD2858 led to cell death in glioma stem cells preventing normal centrosome function and promoting mitotic failure. Normal human astrocytes were not affected by treatment with the inhibitor at submicromolar concentrations. Drug penetration was observed alongside an enhanced effect of clinical radiotherapy doses in vivo. The reported aberrant centrosomal duplication may be a direct consequence of failed cytokinesis suggesting a role of GSK-3 in regulation of mitosis in glioma. GSK-3 is a promising target for combination treatment with radiation in GBM management and plays a role in mitosis-associated events in glioma biology.